DIGITAL INNOVATION FOR TRADITIONAL BATIK CRAFTER - Wibawanto, Wandah; Triyanto,; Cahyono, Agus; Rohendi, Tjetjep Rohidi (PEOPLE: International Journal of Social Sciences, 2020)
Significant market developments demand speed in creating batik motifs. In several studies, it was found that traditional batik craftsmen are still unfamiliar with the use of digital technology in creating batik motifs. So we need a method to introduce digital techniques to traditional craftsmen. This article discusses the use of D-Batik software as an application to accelerate the creation of batik motifs. Using a mixed-method with a field test approach this study aimed to find the fastest method to create the batik motifs. D-Batik was tested on 2 groups of traditional batik crafter in the Semarang. Based on the results of trials, it is known that D-Batik can be easily coordinated by batik craftsmen who are still unfamiliar with technology and are able to produce new motifs with high complexity faster than manual techniques. This study provides technical recommendations for the use of digital technology for traditional craftsmen.